Back Cover Image: Volume 34 Issue 9. Issue 9 (6th September 2019) - Bruckner, Brian A.; Ngo, Uy; Ramchandani, Mahesh; Suarez, Erik; Awad, Samir; Reardon, Michael
Abstract : Back Cover Caption: The cover image is based on the Technical Note Application Techniques of a Novel Hemostat in Cardiac Operations: HEMOBLAST by Brian Bruckner et al., https://doi.org/10.1111/jocs.14171